2017
DOI: 10.1186/s13023-017-0629-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of impaired quality of life in patients with fibrous dysplasia

Abstract: BackgroundFibrous dysplasia is a rare bone disorder, commonly associated with pain, deformity and fractures, which may significantly impact on quality of life. In this study we evaluate quality of life in patients with fibrous dysplasia using the Short Form-36 and the Brief Pain Inventory questionnaires. Data were compared with those of the general Dutch population.ResultsOut of 138 patients from a cohort of 255 patients with fibrous dysplasia that were sent questionnaires assessing quality of life and pain, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 17 publications
4
30
0
1
Order By: Relevance
“…Consistent with previous studies, (4,28) we observed that pain is more frequent and severe in adults compared with pediatric subjects with FD. A novel finding from this study was that BTM levels did not vary according to the presence or absence of pain.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies, (4,28) we observed that pain is more frequent and severe in adults compared with pediatric subjects with FD. A novel finding from this study was that BTM levels did not vary according to the presence or absence of pain.…”
Section: Discussionsupporting
confidence: 93%
“…As part of the protocol used in our ongoing study addressing various aspects of QoL in patients with FD [ 1 , 4 ], three different questionnaires were sent to 255 consecutive patients with a confirmed diagnosis of FD, aged ≥ 16 years, who attended the outpatient clinic of the Centre for Bone Quality of the Leiden University Medical Center between 2013 and 2016. Ninety-two of 138 eligible patients completed the questionnaires, representing a response rate of 67% (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaires used were the Utrecht Coping List Questionnaire (UCL) to evaluate coping strategies, and the Short Form-36 (SF-36) and Brief Pain Inventory (BPI) questionnaires to evaluate QoL [ 15 – 18 ]. For a detailed description of the SF-36 and BPI please refer [ 1 ]. The UCL is a widely used validated questionnaire to study coping strategies, which is based on the assumption that individuals prefer a certain way of coping, regardless of the situation: the coping strategy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of Life (QoL) has been reported to be more severely affected in patients with the more severe types of FD. Determinants of severe disease including a High Skeletal Burden Score (SBS) and increased bone turnover markers (BTM), have been identified as determinants of impaired QoL [ 2 , 3 ]. Other factors than those directly related to the disease which also influence QoL are ‘illness perceptions’: the thoughts and emotions that a patient has concerning his or her disease and its treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%